Monitoreo de material particulado pm 2.5 en el area de influencia de las vias principales de la ciudad de Catamayo - Bernal Jumbo, Carmen Dalila (2024)
The emission of particulate matter 2.5 (PM2.5) in Catamayo is a significant problem, related to activities such as unpaved roads, accumulation of garbage, abandoned buildings and areas devoid of vegetation. This research focused on determining the vehicular load, monitoring the concentrations of particulate matter 2.5 and analyzing the spatial distribution in the main roads of the city of Catamayo. The main roads included the Troncal de la Sierra - Panamericana Sur Ecuador highway, taken as reference points on the route from the city of Loja to Catamayo; Avenida Isidro Ayora, as reference points on the route from the park in downtown Catamayo to the Gasolinera GasoSilva traffic circle on the way to the coast; Avenida Eliseo Arias Carrión Ecuador, as reference points on the lateral route from the traffic circle at the entrance to Catamayo to Gonzanamá. Six points were selected along the three main roads for the vehicle count, registering an average of 5355 vehicles per day in the lateral sector. PM2.5 monitoring was conducted by the automatic method using an Arduino sensor continuously at one point per main road. During one month, alternating monitoring repetitions were performed for each point, each monitoring was performed for 24 hours, along with wind speed and temperature data collection. In general, it was identified that Eliseo Arias Carrión Avenue, specifically on the lateral route, recorded higher concentrations of particulate matter, reaching values of 87.5 ug/ and 62 ug/, exceeding the environmental limits. The spatial distribution, analyzed by kernel interpolation, determined a higher particle density in the lateral sector, with an average of 23.04 ug/ and radius of 425 m.